2014
DOI: 10.1111/vcp.12147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the canine urinary proteome

Abstract: The results of this study illustrate the potential of the dog as an animal model for human disease states and provide the framework for future studies of canine renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…There was a distinct trend away from using the historically popular retro‐orbital sinus/plexus as evolving animal welfare standards continue to encourage the use of other collection routes; a single laboratory indicated that they collect from the retro‐orbital plexus in rats. It has also been reported that CP endpoints are often impacted by the phlebotomy site, highlighting the importance of maintaining consistency within a given study and the need for site‐specific historic control ranges . In mice, routine terminal blood collections were mostly sampled from the vena cava and abdominal aorta (56%), or by cardiac puncture (31%) at necropsy.…”
Section: Phlebotomy Volumes Sites and Methods Of Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was a distinct trend away from using the historically popular retro‐orbital sinus/plexus as evolving animal welfare standards continue to encourage the use of other collection routes; a single laboratory indicated that they collect from the retro‐orbital plexus in rats. It has also been reported that CP endpoints are often impacted by the phlebotomy site, highlighting the importance of maintaining consistency within a given study and the need for site‐specific historic control ranges . In mice, routine terminal blood collections were mostly sampled from the vena cava and abdominal aorta (56%), or by cardiac puncture (31%) at necropsy.…”
Section: Phlebotomy Volumes Sites and Methods Of Collectionmentioning
confidence: 99%
“…This approach is commonly employed to generate large quantities of calibration material for use in quality control testing. Sample pooling has also been utilized for mechanistic investigations such as expanded immunotoxicity testing (when primary indicators of immunotoxicity are positive) or broad characterization of the urinary proteome across multiple canine breeds …”
Section: Sample Poolingmentioning
confidence: 99%
See 2 more Smart Citations
“…In veterinary medicine proteomics were performed in such conditions as canine lymphoma [10] and heartworm disease [11] while canine DCM has not yet been studied using proteomics. In addition, although proteomics were performed in several canine body fluids such as cerebrospinal fluid [12] , urine [13] , bronchoalveolar lavage fluid [14] and follicular fluid [15] , no data have yet been presented on ascitic fluid in dogs with DCM. In the present study, we hypothesized that many of the serum proteomes with low abundance and low molecular weight may have roles in the development of DCM in dogs.…”
Section: Introductionmentioning
confidence: 99%